THE INFLUENCE OF PRICE, ADVERTISING AND IMAGE OF KAWASAKI NINJA R ON CONSUMER BUYING INTEREST IN BANDUNG CITY - Sukma, Andhi; Maya Dora, Yenny (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of prices, advertisements, and Kawasaki Ninja R brand image on consumer purchase intentions in the city of Bandung. The factors tested in this study are price, advertising, and brand image as independent variables. Whereas purchase intention is the dependent variable. The research methods used in this research are descriptive and verification methods. The population in this study are people who intend to have Kawasaki Ninja R. The sampling technique used in this study is non-probability sampling using a purposive sampling technique with a sample size of 75 respondents. While the analytical method used in this study is multiple linear regression analysis and the coefficient of determination is at a significant level of 5%. The program used in analyzing data uses Statistical Package for Social Sciences (SPSS) Ver. 24.00 The results showed that the variable price (X1) influenced the purchase intention. Furthermore, the Ad variable (X2) influences the purchase intention and the brand image variable (X3) influences the purchase intention. Price, advertising and brand image simultaneously influence purchase intention.